ARSITEKTUR METABOLISME JEPANG - SARI, DIAN PERWITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Architecture of Japan Metabolism born during World Design Conference 1960 in Japan, a movement led by Kenzo Tange as a mentor and Kisho Kurokawa as as a leader of the movement then, Fumihiko Maki and Kiyonori Kikutake as its members, Arata Isozaki as Tange students also participated in this movement, although not as formally member of Metabolist. This study aimed to formulate the architecture of Japan Metabolism conceptually by constructed the concept of Metabolism Architecture that raised by figures of Metabolic movement there are Kenzo Tange, Kiyonori Kikutake, Kisho Kurokawa, Fumihiko Maki and Arata Isozaki. The research method of this study used the content analysis method, is the research techniques to describe objectively, systematically and contents quantity of communication that appeared (manifest) and determined the conclusion of the text. The case studies include the overall of works that built and unbuilt from the Metabolist that are Kenzo Tange, Kiyonori Kikutake, Kisho Kurokawa, Fumihiko Maki and Arata Isozaki, and then examined the characteristics, the principles of design, and the factors underlying emergence metabolism architecture. The research resulted conceptually seen the metabolism process in Architecture of Japan Metabolism described a process \"connector\" system connection that connected characteristics different elements that occurs spontaneous or planned and then generated energy that could making process of \"growth\", \"changed\", \"regeneration\" and \"ruined\" that occurs in architecture and city. This process happened continuously.